Inhaled formaldehyde induces DNA–protein crosslinks and oxidative stress in bone marrow and other distant organs of exposed mice. (18th October 2013) - Ye, Xin; Ji, Zhiying; Wei, Chenxi; McHale, Cliona M.; Ding, Shumao; Thomas, Reuben; Yang, Xu; Zhang, Luoping
Abstract : Formaldehyde (FA), a major industrial chemical and ubiquitous environmental pollutant, has been classified as a leukemogen. The causal relationship remains unclear, however, due to limited evidence that FA induces toxicity in bone marrow, the site of leukemia induction, and in other distal organs. Although induction of DNA–protein crosslinks (DPC), a hallmark of FA toxicity, was not previously detected in the bone marrow of FA‐exposed rats and monkeys in studies published in the 1980s, our recent studies showed increased DPC in the bone marrow, liver, kidney, and testes of exposed Kunming mice. To confirm these preliminary results, in the current study we exposed BALB/c mice to 0, 0.5, 1.0, and 3.0 mg m −3 FA (8 hr per day, for 7 consecutive days) by nose‐only inhalation and measured DPC levels in bone marrow and other organs of exposed mice. As oxidative stress is a potential mechanism of FA toxicity, we also measured glutathione (GSH), reactive oxygen species (ROS), and malondialdehyde (MDA), in the bone marrow, peripheral blood mononuclear cells, lung, liver, spleen, and testes of exposed mice. Significant dose‐dependent increases in DPC, decreases in GSH, and increases in ROS and MDA were observed in all organs examined (except for DPC in lung). Bone marrow was among the organs with the strongest effects for DPC, GSH, and ROS. In conclusion, exposure of mice to FA by inhalation induced genotoxicity and oxidative stress in bone marrow and other organs. These findings strengthen the biological plausibility of FA‐induced leukemogenesis and systemic toxicity. Environ. Mol. Mutagen. 54:705–718, 2013. © 2013 Wiley Periodicals, Inc.